Handgrip strength and muscle quality in Australian women: cross‐sectional data from the Geelong Osteoporosis Study. Issue 3 (15th February 2020) - Sui, Sophia X.; Holloway‐Kew, Kara L.; Hyde, Natalie K.; Williams, Lana J.; Tembo, Monica C.; Mohebbi, Mohammadreza; Gojanovic, Marlene; Leach, Sarah; Pasco, Julie A.
Abstract: Background: Low handgrip strength (HGS) is a measure of poor skeletal muscle performance and a marker of ill health and frailty. Muscle quality (MQ) is a measure of muscle strength relative to muscle mass. We aimed to develop normative data for HGS and MQ, report age‐related prevalence of low HGS and MQ, and determine the relationship with age, anthropometry, and body composition for women in Australia. Methods: This cross‐sectional analysis included data from 792 women (ages 28–95 years) assessed by the Geelong Osteoporosis Study. Duplicate measures of HGS were performed for each hand with a dynamometer (Jamar) and the mean of maximum values used for analyses. Dual energy X‐ray absorptiometry‐derived lean mass for the arms was used to calculate MQ as HGS/lean mass (kg/kg). Body mass index (BMI) was categorized as normal (BMI < 25.0 kg/m 2 ), overweight (25.0–29.9 kg/m 2 ), and obese (> 30.0 kg/m 2 ). Fat mass index (FMI) was calculated as whole body fat/height 2 (kg/m 2 ) and appendicular lean mass index (ALMI) as lean mass of arms and legs/height 2 (kg/m 2 ). Results: Mean (±SD) of HGS values for normal BMI, overweight, and obese groups were 25 (±7), 24 (±7), and 24 (±7) kg, P = 0.09, and for MQ, 12 (±3), 11 (±3), and 10 (±3) kg/kg, P < 0.001. Our data indicated a quadratic relationship between age and HGS or MQ. Mean HGS and MQ remained stable until the fifth age decade then declined steadily with increasing age; therefore, we used data for women ( n = 283) aged 28–49 years as the young adult reference group, with mean (SD) values for HGS 28 (±6) kg and MQ 12 (±3) kg/kg. The prevalence of low ( T ‐score < −2) HGS and MQ for women 80 years and older was 52.2% and 39.6%, respectively. In multivariable models, age‐adjusted HGS was associated with FMI ( B = −0.13, P = 0.004) and ALMI (1.03, <0.001) while age‐adjusted MQ was associated with BMI (−0.15, <0.001) but not with FMI. In a sensitivity analysis, the same pattern remained after the removal of 129 women who reported hand and/or arm pain. Conclusions: Mean HGS and MQ declined with advancing age in older women. Our data suggest that while mean HGS increased with appendicular lean mass and decreased with body fat mass, there was no association with BMI. By contrast, MQ decreased with increasing BMI, but not with increasing adiposity.